(1→3)-β-D-glucanemia in deep mycosis. Issue 4 (1997) - Obayashi Obayashi, Taminori Taminori
Abstract : Factor G, a coagulation proenzyme of the Japanese horseshoe crab ( Tachypleus tridentatus ), is extremely sensitive to (1→3)-β-D-glucan, which is a characteristic cell-wall constituent of fungi. Using this factor and by a digestion study with (1→3)-β-D-glucan, we showed that blood from patients with deep m ycosis contains the glucan. It was detected in 39 out of 41 fungal febrile episodes (sensitivity 90%), but in none of the 59 nonfungal febrile episodes (specificity 100%).